Variation in the attached community structure and function of artificial habitats during ecological succession: A case study of the artificial reef area in Bailong Pearl Bay, China - Li, Ruolin; Guo, Yu; Zhang, Ankai; Zhang, Shuo; Zhang, Hui; Qin, Chuanxin (Frontiers in Marine Science, 2022)
With the continuous development of ports, ship transportation, resource extraction and artificial habitat deployment, an increasing number of artificial structures have created new usable spaces for marine organisms, and the biological communities living on their surfaces have undergone ecological succession. However, related studies have ignored ecological functions, interspecific relationships, and stability in different successional stages. Based on traditional taxonomy, this study applied functional diversity, niche overlap and niche breadth indexes to compare the attached organisms on artificial reefs (ARs) with different construction times in Bailong Pearl Bay, Fangchenggang City, Guangxi Zhuang Autonomous Region, China. The change trends of richness, habitat resource supply, resource utilization degree and efficiency, and interspecific relationships during the succession process were analysed. The results indicated that richness increased with functional diversity. While the number of species increased, the attached organisms showed different functional characteristics, and the number of species with identical traits decreased. The attached community in the later stage of development had a higher degree of utilization of ecological space, more comprehensive and efficient utilization of effective resources, a stronger degree of complementarity of organismal niches, and weaker interspecific competition. In the early stage of the developmental process, the attached community was affected by more environmental factors and had very significant correlations with those factors. The combination of the niche overlap index and the niche breadth index indicated that the resource supply supporting the survival and development of the attached organisms on the ARs with earlier construction times may be greater. The decrease in the number of biomarkers, the similarity of biomarkers belonging to the same family, and the similarity of dominance alternation all indicated that during the process of long-term development and community succession, the organisms attached to the various parts of the ARs tended to become more similar.